Impact of lockdown Covid-19 pandemic on himalayan environment. Issue 2 (26th January 2023) - Bahukhandi, Kanchan; Agarwal, Shilpi; Singhal, Shailey
ABSTRACT: The COVID-19 Pandemic have caused severe impact on lives in various ways, but our environment has experienced a positive outcome due to the lockdown which was imposed all over world including Himalayan region of India. The worldwide spread of COVID 19 has reduced movement of vehicles, industries and all tourism activities. Due to shutdown of all the commercial activities and traffic has helped the environment to reclaim naturally. The Himalayas is one of the world's most fragile and sensitive hotspots to global climate change, with impacts manifesting at a particularly rapid rate. The Himalayan glaciers are the water towers of Asia, and the source of many of the world's great rivers. In this research paper, an attempt has been made to describe the improvement in physiochemical characteristics of surface water, all parameters were compared with BIS standard of drinking water quality during pre lockdown and lockdown period. The ambient air quality have also been significantly improved and noise level were also found under permissible limit of Ambient air quality Standard.